If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(12 + -2y) + 2y = 8 (12 * 3 + -2y * 3) + 2y = 8 (36 + -6y) + 2y = 8 Combine like terms: -6y + 2y = -4y 36 + -4y = 8 Solving 36 + -4y = 8 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + -4y = 8 + -36 Combine like terms: 36 + -36 = 0 0 + -4y = 8 + -36 -4y = 8 + -36 Combine like terms: 8 + -36 = -28 -4y = -28 Divide each side by '-4'. y = 7 Simplifying y = 7
| 2x^2-37x+66=0 | | -8-12y+5=15 | | 4q-q-(2q-3)= | | 3x+1x=15 | | 3x+1x=20 | | 3x+1x=1 | | 7(5-3x)+5(5x-3)= | | 4x^2-2x=80 | | (9y+5)-(7y-3)= | | 66+17y=17 | | 5x=x^2+6 | | x+2x+3x+3=15 | | 2(8+2c)=32 | | 30+5t=80 | | 12x-8=3x+28 | | x+2+3x+3=15 | | 2(5y+6)-4(y-8)= | | 2x^2+2=2 | | n-3/4+n+5/7=5/14 | | 0.5x+x=x | | 0.5x+x=y | | 0.5x+x=1.5x | | 8(r+2)=64 | | (-2ab^2)(5a^3b^4)= | | 5(3c+2)=70 | | -4(1-7a)+5=-8a-39 | | 13+c^2=77 | | 1/8+5/6= | | 3x(6x)= | | -6p-6-15p=5p-20-38 | | 2x^2+10x-126=0 | | 6-3x=6x-8x-6 |